Socialni kapital na slovenskem podeželju - Potočnik Slavič, Irma (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2009)
In the last two decades, the concept of social capital has become very popular amongst researchers and in politics as well. Its measurement is very complex in spite of relatively simple and apparently useful concept. Analysis of social capital indicators in selected Slovenian rural areas (Upper Savinja Valley, Suha krajina, Goriška brda, Brkini) have demonstrated its positive impact on local community capacity building, being the starting point for activation of endogenous development potentials.
Keywords: podeželje; prebivalstvo; rural area; Slovenia; Slovenija; socialna geografija; socialni kapital